THE INTERACTION OF TUNGSTEN (VI) OXIDE AND CALCIUM TUNGSTATE IN THE CaCl2–NaCl EUTECTIC MELT - Medvezhynska, Olha; Omel'chuk, Anatoliy; Shvaika, Irine; Shvayka, Igor; Proskurka, Lubov (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2023)
The interaction of tungsten (VI) oxide and calcium tungstate with a molten eutectic mixture of calcium-sodium chlorides in the temperature range from 600 to 800 °С was investigated by the methods of isothermal saturation, mass spectrometry with inductively coupled plasma (ICP–MS) and X-ray phase analysis. It was noted that the solubility of both tungsten trioxide and calcium tungstate depends to a large extent on temperature. Thus, in the temperature range from 600 to 700 °C, the equilibrium concentration of tungsten increases by an average of 1.7 times, and in the range from 700 to 800 °C, its values increase by 3.9 times. Based on the results obtained by inductively coupled plasma mass spectrometry, it was found that the equilibrium content of tungsten (in the calculation of pure metal) in the molten eutectic mixture of sodium and calcium chlorides both in contact with tungsten trioxide and in contact with calcium tungstate at different temperatures within the error of definition has approximately the same values. The obtained results indicate in favor of the fact that the dissolution of tungsten trioxide in the molten mixture of sodium and calcium chlorides proceeds through the stage of formation of calcium tungstate. It is possible that sodium tungstate may be formed in this case, but no direct evidence of this has been found. At temperatures higher than 750 °C, almost all of the loaded tungsten trioxide turns into calcium tungstate. This gives grounds for asserting that in the molten salt phase tungsten is mainly in the form of calcium tungstate. The obtained results give reason to consider that the interaction of the mentioned oxygen-containing compounds of tungsten produces homogeneous salt phases of the ternary system CaCl2–NaCl–CaWO4, the content of which calcium tungstate in the temperature range of 700÷800 °С is satisfactorily described by the dependence ln S = 8.331 – 14057/T.